Impact of interannual and multidecadal trends on methane-climate feedbacks and sensitivity - Cheng, Chin-Hsien (2023)
We estimate the causal contributions of spatiotemporal changes in temperature (T) and precipitation (Pr) to changes in Earth's atmospheric methane concentration (CCH4) and its isotope ratio δ13CH4 over the last four decades. We identify oscillations between positive and negative feedbacks, showing that both contribute to increasing CCH4. Interannually, increased emissions via positive feedbacks (e.g. wetland emissions and wildfires) with higher land surface air temperature (LSAT) are often followed by increasing CCH4 due to weakened methane sink via atmospheric •OH, via negative feedbacks with lowered sea surface temperatures (SST), especially in the tropics. Over decadal time scales, we find alternating rate-limiting factors for methane oxidation: when CCH4 is limiting, positive methane-climate feedback via direct oceanic emissions dominates; when •OH is limiting, negative feedback is favoured. Incorporating the interannually increasing CCH4 via negative feedbacks gives historical methane-climate feedback sensitivity ≈ 0.08 W m-2 °C-1, much higher than the IPCC AR6 estimate.